Trifluoromethyloxadiazoles: inhibitors of histone deacetylases for control of Asian soybean rust - Winter, Christian; Fehr, Marcus; Craig, Ian R; Grammenos, Wassilios; Wiebe, Christine; Terteryan‐Seiser, Violeta; Rudolf, Georg; Mentzel, Tobias; Quintero Palomar, Maria Angelica (Pest management science, 2020)
BACKGROUND Trifluoromethyloxadiazoles (TFMOs) are selective inhibitors of class II histone deacetylases (HDACs). To date, class II HDACs have not been addressed as target enzymes by commercial fungicides. RESULTS Antifungal testing of a broad variety of TFMOs against several important plant pathogens showed activity against only rusts, and especially Phakopsora pachyrhizi, the cause of Asian soybean rust. A structure–activity relationship was established, leading to highly active fungicides that inhibit fungal class II and HOS3‐type HDACs of Aspergillus nidulans. Studies of the enzyme–inhibitor binding mode using protein structural information based on the crystal structure of human HDAC4 argue that TFMOs inhibit these enzymes only after undergoing hydration. CONCLUSION Fungal class II HDACs are potential target enzymes for the control of at least some biotrophic crop diseases, in particular Asian soybean rust. As with any novel mode‐of‐action, class II HDAC fungicides would offer the potential to control fungal isolates that show reduced sensitivity toward existing commercial fungicides. Trifluoromethyloxadiazoles have been found to be inhibitors of fungal class IIa histone deacetylases with high antifungal activity against obligate biotrophic rust diseases. This chemical class exhibits a novel mode‐of‐action for fungicides. © 2020 Society of Chemical Industry